Denver goes to the movies: engaging national-scale identity shifts from movie house to movie palace, 1900-1940 - Frank, Nichelle, author; Orsi, Jared, advisor; Ore, Janet, committee member; Dickinson, Greg, committee member (Colorado State University. Libraries, 2012)
This thesis examines the relationship between film history and movie theater architecture at local and national levels as a window into early twentieth century identity shifts. The argument is that Denver films and movie theaters from 1900 to 1940 manifested national-level identity shifts as well as influenced them. The identity shifts included attitudes of innovation, decadence, and endurance that roughly characterized the 1900s and 1910s, 1920s, and 1930s. These identities represented the dominant identities that were part of the broad shift from nineteenth century frontier identity to post-WWII modern identity. This thesis draws from Denver newspapers, architectural and cinema journals, early film histories, Denver Householder and City Directories, Denver Sanborn Fire Insurance maps, other historic maps, memoirs, and photographs. Through close study of these sources and balancing the national history with Denver history, there emerges a story of how Denverites and Americans have selected ideals to maintain and adopted others as they chase their ever-changing dreams.
Keywords: architecture; Colorado; Denver; film history; identity; movie theaters